2020
DOI: 10.1007/s13205-020-02432-w
|View full text |Cite
|
Sign up to set email alerts
|

AuNPs/CNF-modified DNA biosensor for early and quick detection of O. tsutsugamushi in patients suffering from scrub typhus

Abstract: A novel approach has been developed for the detection of 56 kDa tissue-specific antigen (TSA) gene of Orientia tsutsugamushi a causative agent of scrub typhus disease. The approach was developed by immobilization of 5′ NH2 labeled ssDNA probe selective to 56 kDa TSA gene, to the surface of AuNPs/CNF modified screen-printed electrode. An electrochemical response was recorded with single stranded genomic DNA (ssDNA) of O. tsutsugamushi isolated from patient sample, using cyclic voltammetry and electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…The electrode was characterized at a different phase of the sensor development, including the bare electrode and ssDNA probe-modified electrode, and after hybridization of the DNA sensor (DNA Probe) with ssGDNA of L. interrogans. Fourier-transform infrared spectroscopy (FTIR) and Raman spectroscopy were carried out to ensure each step of the DNA sensor development process [ 16 ]. FTIR studies revealed the functional groups imparted on the working electrode (AuN/CNF) after the modification with the ssDNA (probe) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrode was characterized at a different phase of the sensor development, including the bare electrode and ssDNA probe-modified electrode, and after hybridization of the DNA sensor (DNA Probe) with ssGDNA of L. interrogans. Fourier-transform infrared spectroscopy (FTIR) and Raman spectroscopy were carried out to ensure each step of the DNA sensor development process [ 16 ]. FTIR studies revealed the functional groups imparted on the working electrode (AuN/CNF) after the modification with the ssDNA (probe) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The limit of detection (LOD) of the DNA sensor was determined as 0.0077 ng/µL, which was in agreement with the experimental value (minimum ssGDNA concentration). An increase in the Ip value with different concentrations of L. interrogans GDNA was due to the presence of guanine bases on the DNA sensor surface, which showed a binding affinity with methylene blue (MB) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease is highly prevalent in rural areas, where proper diagnosis facilities are not available to detect the infection at early stages resulting in higher mortalities. The clinical symptoms of the disease are very common and similar to the other infections that make it difficult to diagnose [ 1 , 3 ]. The bacteria spread through the infected larval mite that produces eschar at the biting site.…”
Section: Introductionmentioning
confidence: 99%